The Role of Non-coding RNAs in Diabetic Nephropathy-Related Oxidative Stress - He, Xiaoyun; Kuang, Gaoyan; Zuo, Yi; Li, Shuangxi; Zhou, Suxian; Ou, Chunlin (Frontiers in Medicine, 2021)
Diabetic nephropathy (DN) is one of the main complications of diabetes and the main cause of diabetic end-stage renal disease (ESRD), which is often fatal. DN is usually characterized as progressive renal interstitial fibrosis, which is closely related to the excessive accumulation of extracellular matrix and oxidative stress. Non-coding RNAs (ncRNAs) are RNA molecules expressed in eukaryotic cells that cannot be translated into proteins. They are widely involved in the regulation of biological processes, such as chromatin remodeling, transcription, post-transcriptional modification, and signal transduction. Recent studies have shown that ncRNAs play an important role in the occurrence and development of DN and participate in the regulation of oxidative stress mechanisms in DN. This review clarifies the function and mechanism of ncRNAs in DN-related oxidative stress mechanisms, providing valuable insights into the prevention, early diagnosis, and molecular therapeutic targets of DN.